Conquests of Egypt: making history in ʿAbbāsid Egypt - Zychowicz-Coghill, E (2017)
This dissertation is a study of the Futūḥ Miṣr (Conquest of Egypt) of Ibn 'Abd al-Ḥakam (d. 257/871), the earliest extant Arabic history of Egypt. Its primary aim is not to assess whether its information is 'authentic' – i.e. corresponding to an objective historical reality – though my findings are of relevance for those engaged in debates over authenticity. My goal instead is to explore the ideas about the past which are conveyed by this particular conglomeration of historical information and to propose methods through which we can expose and analyse different layers and types of authorial activity within a multi-vocal text like Futūḥ Miṣr. Ultimately, I use this analysis as the basis of a case study suggesting how we might more effectively historicise the generation and transmission of historical ideas in the early Islamic period. Part I of the thesis consists of three chapters which explore Futūḥ Miṣr as a whole, literary text which can be understood as an instantiation of the historical worldview of its composer. Part II of the thesis contains three chapters which each illuminate features of Ibn 'Abd al-Ḥakam's historical practice which are important prerequisites for the stratigraphic reading of Futūḥ Miṣr performed in Part III. Part III of the thesis uses the understanding of Ibn 'Abd al-Ḥakam's authorial techniques developed in Part II to expose the earlier packages of historical information which underpin Futūḥ Miṣr. These final three chapters demonstrate how Ibn 'Abd al-Ḥakam reinvested these pre-existing narratives with meaning at a micro-level – by interjecting commentary and accounts from other sources – and at a macro-level – by integrating them into the larger narrative structure of Futūḥ Miṣr. In sum, this thesis is the first systematic study of the sources, structure, and authorship of an early Arabic history, which both tests and expands our current understanding of the dynamics of early Islamic historical writing, and sheds light on numerous aspects of the changing uses of the past among the Muslim scholars of Umayyad and ʿAbbāsid Egypt.